A study of how well online teaching and learning methods work for students at universities and colleges - Zainudin, Mohd Izyan Suhaili; Subari, Kamalularifin; Aripin, Muhamad Afzamiman; Arshad, Bazilah; Mustafa, Zaiton; Mohamed Yusof, Nazeema; Magiman, Mohamad Maulana; Anal, Ardzulyna (AnKa Publisher, 2022)
More than a decade has passed since internationally recognized universities and colleges began using online teaching and learning methods to fulfill the needs of students who reside a long distance away from their places of higher education. Internet teaching and learning proved to be a lifesaver for many educational institutions and students during the COVID-19 outbreak in 2014. Students from universities and colleges around the country are participating in a poll to determine the success of online teaching and learning. An online survey will be conducted, and the findings will be made available to the community. It was decided to do this by developing a questionnaire circulated among college and university students. Approximately 500 students from various universities, engineering schools, and medical institutions participated in and submitted the survey results. In a study, it was discovered that the use of animation, digital collaboration with peers, video lectures by subject-matter experts, multiple-choice questions in online quizzes, student version software, a conducive learning environment at home, interactions by professors during lessons, and online materials provided by faculty could all help to improve online learning. Since they may all view PowerPoint presentations in front of them at any volume level, they wish while in an internet based classroom, students no longer have to walk or drive to class when in an internet-based classroom.